Football in Ottoman Macedonia - Minov, Nikola; Sarakinski, Vojislav (Здружение на историчарите на Република Македонија, Скопје, 2021)
This article aims to explore the extant sources documenting the emergence of organised football in Ottoman Macedonia – mainly newspaper articles and notes by local chroniclers. In Ottoman Macedonia, football was mainly played in Salonica by the sons of the Jewish, Greek, and Western bourgeoisie, and in Bitola by the sons of rich Aromanians; after the Young Turk Revolution, it was played by western-educated Turkish officers in Skopje and Bitola, and by some citizens of Naoussa, Veria and Edessa in southwest Macedonia. The sport may have made a late start, but it walked the same route as football in Great Britain and Western Europe did. It started as a sport for the city élite, who quickly got fed up with the novelty and turned to seeking new thrills in other sports; had it not been for the Balkan Wars and WWI, football would have probably become a real working- class sport as early as the 1910s – as it did during the Interwar period in the former territories of Ottoman Macedonia that became part of Greece, Bulgaria and the Kingdom of Serbs, Croats and Slovenes.
Keywords: football, Salonica, Union Sportive, Omilos Philomousson, Audax, Championship, Intercalated Olympic Games, Bitola, Skopje, Naoussa